College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter R - Section R.5 - Factoring Polynomials - R.5 Exercises: 103



Work Step by Step

We factor: $x^{6}-2x^{3}+1=(x^{3}-1)(x^3-1)=(x^3-1)^2 =[(x-1)(x^{2}+x+1)]^{2} =(x-1)^{2}(x^{2}+x+1)^{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.